Comparison of three methods for measuring psoriasis severity in clinical studies (Part 2 of 2): use of quality of life to assess construct validity of the Lattice System Physician's Global Assessment, Psoriasis Area and Severity Index and Static Physician's Global Assessment. (27th April 2015) - Simpson, M.J.; Chow, C.; Morgenstern, H.; Luger, T.A.; Ellis, C.N.
Abstract Background Systems for determining psoriasis severity in clinical trials have not been sufficiently validated against patients' perceived quality of life. Objective To validate three systems of physician‐determined psoriasis severity (the Lattice System Physician's Global Assessment [LS‐PGA], Psoriasis Area and Severity Index [PASI] and static Physician's Global Assessment [sPGA]). Methods Data were from a 24‐week randomized, double‐blind, placebo‐controlled, multicenter trial of therapy with oral calcineurin inhibitors in 445 patients. Construct validity was measured by correlations of the three severity scores with patients' self‐reported quality of life (QoL) from the Dermatology Life Quality Index (DLQI) and a DLQI item about psoriasis symptoms. Results All severity systems were moderately and positively correlated with QoL, indicating construct validity. QoL was most consistently related to physicians' assessments of body surface area involved with psoriasis (iBSA) followed by, in the order of consistency, plaque elevation, erythema and scale. Conclusions The LS‐PGA weights iBSA and aspects of plaque morphology in concert with their relative effects on QoL. The LS‐PGA, sPGA and PASI are validated by their relationship to QoL in a clinical trial.